The Influence Of Both External And Internal Elements On Organizational Performance In The Moderation Of Organizational Culture - Bambang Jatmiko; Titi Laras; Wahyu Manuhara Putra (SEAN Institute, 2024)
The objectives of this research are: a). To empirically test and prove the influence of the Accounting Information System on organizational performance in MSMEs in the Special Region of Yogyakarta; b). To empirically test and prove the influence of the Internal Control System on organizational performance in MSMEs in the Special Region of Yogyakarta; c). To empirically test and prove the influence of Information Technology on organizational performance in MSMEs in the Special Region of Yogyakarta; d).To empirically test and prove that Organizational Culture moderates the influence of the Accounting Information System on organizational performance in MSMEs in the Special Region of Yogyakarta; e). To empirically test and prove that Organizational Culture moderates the influence of the Internal Control System on organizational performance in MSMEs in the Special Region of Yogyakarta; f).To empirically test and prove that Organizational Culture moderates the influence of Information Technology on organizational performance in MSMEs in the Special Region of Yogyakarta. The survey approach is used in the research process. The survey method is a technique that uses written and spoken surveys to gather primary data. According to the research's findings, there are several factors that affect how well MSMEs in the Special Region of Yogyakarta perform, including: a) Accounting Information Systems; b) Internal Control Systems; c) Information Technology; d) Organizational Culture, which attenuates the relationship between Accounting Information Systems and Organizational Performance; and e) Organizational Culture, which attenuates the relationship between the Internal Control System and Organizational Performance.